2021
DOI: 10.12890/2021_002763
|View full text |Cite
|
Sign up to set email alerts
|

Giant Metastatic Breast Phyllodes Tumour with an Elusive Diagnosis: A Case Report and Literature Review

Abstract: Background: The term phyllodes tumours, which account for less than 1% of breast neoplasms, describes a spectrum of heterogenous tumours with different clinical behaviours. Less than 30% present as metastatic disease. Complete surgical resection is the standard of care so that recurrence rates are reduced. The role of adjuvant chemotherapy or radiation therapy is controversial. Patients with metastatic disease have a median overall survival of around 30 months. Case description: The authors present the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Los autores presentan también el caso de una mujer de 57 años de edad con un tumor filoides maligno izquierdo exuberante con afectación bilateral, además de metástasis pulmonares y axilares. La paciente se sometió a radioterapia hemostática e inició quimioterapia paliativa con doxorrubicina, consiguiendo respuesta parcial con mejoría significativa en la calidad de vida (17). En una revisión sistemática y metanálisis que tuvo como objetivo investigar las tasas de recurrencia local (LR) entre los tres tipos de tumores filoides, se obtuvo los siguientes resultados: La revisión incorporó 54 estudios con 9234 casos individuales.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Los autores presentan también el caso de una mujer de 57 años de edad con un tumor filoides maligno izquierdo exuberante con afectación bilateral, además de metástasis pulmonares y axilares. La paciente se sometió a radioterapia hemostática e inició quimioterapia paliativa con doxorrubicina, consiguiendo respuesta parcial con mejoría significativa en la calidad de vida (17). En una revisión sistemática y metanálisis que tuvo como objetivo investigar las tasas de recurrencia local (LR) entre los tres tipos de tumores filoides, se obtuvo los siguientes resultados: La revisión incorporó 54 estudios con 9234 casos individuales.…”
Section: Resultsunclassified
“…Un metanálisis informa tasas de recurrencia local del 8 % para los tumores benignos, 13 % para los borderline y 18 % para tumores malignos, respectivamente (16). La afectación de los ganglios linfáticos axilares es rara, incluso cuando los tumores son malignos, por lo que la disección axilar no es obligatoria (17). En los casos de las pacientes con tumores filoides malignos y enfermedad metastásica, la mediana de supervivencia general es de aproximadamente 30 meses.…”
Section: Introductionunclassified
“…Koh et al [26] showed that a combination of large tumor size (≥90 mm) ant the presence of malignant heterologous elements had a statistically significant association with the development of distant metastasis. Most frequently, malignant PTs metastasize to the lung, bones, brain, and liver [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Few rare distant metastatic sites are the adrenal glands [20] , kidney [13] , skin [27] , ovary [28] , heart [29] , pleura [30] , oral cavity [31] , duodenum [32] , pancreas [33] , tonsillar [12] , and para-aortic nodes [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy effects in PTs treatment are lacking because of insufficient data from large prospective studies. In our literature review of patient with distant metastasis to the lungs, the most frequent chemotherapy was with Doxorubicin and ifosfamide [ 7 , 10 , [17] , [18] , [19] ]. In 6 studies [ 8 , 12 , [14] , [15] , [16] , 20 ] adjuvant chemotherapy was not given due to controversial effects or patient's request, detailed descriptions are shown in ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation